Analysis of vertical jump, rating of perceived exertion, delayed-onset muscle soreness, and muscular peak power in young male Brazilian football players submitted to plyometric and semi-squat training with weights - Renato Tavares Fonseca; Gustavo Casimiro Lopes; Juliana Brandão Pinto de Castro; Luciano Alonso Valente dos Santos; Bruno Lucas Pinheiro Lima; Gilson Ramos de Oliveira Filho; Rodolfo de Alkmim Moreira Nunes; Rodrigo Gomes de Souza Vale (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study analyzed the effects of plyometric and strength training on vertical jump (VJ), rating of perceived exertion (RPE), delayed-onset muscle soreness (DOMS), and absolute (APP) and relative (RPP) muscle peak power in young male football players. Twenty-five participants were randomly divided into semi-squat training group (SSTG), plyometric training group (PTG), and control group (CG). The duration of the intervention was six weeks. VJ was analyzed with a computerized jumping platform. DOMS and RPE with the Borg’s Visual Analogue Scale (VAS) and the Adapted Borg Scale (ABS), respectively. The SSTG showed improvements (p < 0.05) in countermovement jump (CMJ), squat jump (SJ), APP (3190.67 ± 338.49 W), and RPP (47.75 ± 5.01 W/kg). PTG showed improvements (p < 0.05) in SJ. In the intragroup comparations, SSTG, PTG, and CG showed an increase (p < 0.05) in RPE and DOMS. Between groups, PTG presented an increase (p < 0.05) on RPE and DOMS compared with SSTG and CG. CMJ presented strong correlations between APP and VJ, RPP, and VJ, and APP and RPP. SJ showed a higher positive correlation between all the physical variables. Only SSTG promoted an increase in both types of jumps, with a greater APP and RPP and a lower RPE and DOMS.